In vitro regeneration ability of diploid and autotetraploid plants of Cichorium intybus L. - Ghotbi Ravandi, E.; Rezanejad, F.; Dehghan, E. (Цитология и генетика, 2014)
Polyploidy has played a significant role in the evolutionary history of plants and is a valuable tool for obtaining useful characteristics. Because of the novelty of polyploids, comparison of their in vitro culture responses with diploids would be notable. In this study, leaf explants from diploid, autotetraploid and mixoploid plants of Cichorium intybus L. were cultured in vitro on the similar media and under same conditions. The ploidy level of the obtained calluses and regenerants were determined by flow cytometry analysis. The callogenic response of leaf explants cultured on the callus induction medium did not depend on the ploidy level of their parental plants. According to the flow cytometry analysis, the increased ploidy levels (4x) and (8x) were observed in the callus cultures with diploid and tetraploid origin, respectively. A considerable difference was observed between the ploidy level of mixoploid plants and their calluses, indicating the dominance of diploid cells in the callus tissue. The results showed that polyploidy led to the loss of organogenic potential as the tetraploid origin calluses failed to regenerate, while the diploid origin calluses successfully regenerated to whole plants. Полиплоидия сыграла значительную роль в эволюционной истории растений как ценный инструмент получения полезных признаков. В настоящей работе приведено сравнение культурального ответа in vitro полиплоидов с диплоидами. Листовые экспланты диплоидных, автотетраплоидных и миксоплоидных растений Cichorium intybus L. культивировали на одних и тех же средах в одинаковых условиях. Уровень плоидности индуцированных каллусов и регенерантов определяли с помощью жидкостной цитометрии. Способность листовых эксплантов к каллусообра-зованию на среде для индукции каллуса не зависела от уровня плоидности исходных растений. По данным жидкостной цитометрии в каллусных культурах диплоидного и тетраплоидного происхождения на блюдалось увеличение уровней плоидности (4x и 8x соответственно). Значительные отличия в уровнях плоидности обнаружены у миксоплоидных растений и их каллусов, при этом в каллусной ткани доминировали диплоидные клетки. Показано, что поли плоидия приводила к потере органогенного потенциала, так как тетраплоидные каллусы не были способны к регенерации, а в каллусах диплоидного происхождения успешно происходила регенерация растений.